Development of a multiplex PCR-lateral flow assay for the detection of samonella typhi and salmonella paratyphi A - Zulkiply, Nor Amalina (2014)
Salmonella enterica serovar Typhi and Salmonella enterica serovar Paratyphi A are causative agents of enteric fever and occur each year mostly in underdeveloped and developing countries. The persistence of enteric fever is due to the existence of chronic carriers who harbor the bacteria inside their gall bladder and transmitted the disease through contaminated water and food. Stool culture is the gold standard for the detection of typhoid and paratyphoid carriers but this method is time consuming and requires highly skilled personnel. Therefore, polymerase chain reaction (PCR) assay is a better alternative since it is rapid, highly sensitive and specific, and allows for simultaneous detection of pathogens. Agarose gel electrophoresis followed by UV transilluminator is the common method for the detection of PCR amplicons, but this method is also time consuming, tedious, requires special equipment and highly skilled personnel, and it exposes users to ethidium bromide and ultra violet light. Thus, this study aims to develop a multiplex PCR coupled with lateral flow assay (mPCR-LFA) for the detection of S. enterica ser. Typhi and S. enterica ser. Paratyphi A in the presence of two controls; i) pan-Salmonella as a target gene control and ii) internal amplification control (IAC). Four sets of primers were manually designed based on specific regions of the target genes; stgA gene of S. enterica ser. Typhi, intergenic region (SSPAI) between SSPA1723a and SSPA1724 gene of S. enterica ser. Paratyphi A, ompC gene of Salmonella serovars and hemM gene of Vibrio cholerae as an IAC. The target genes and the similar sequences obtained from BLASTn program were aligned using ClustalW Multiple Alignment (BioEdit software). Forward primers were labeled with FITC, Texas Red, DNP and DIG at the 5’end, while reverse primers were labeled with biotin at the 5’end for the purpose of detection using lateral flow assay. After amplification, labeled PCR amplicons were applied onto the lateral flow strip and bound to their respective capture reagents immobilized on the membrane (anti-FITC, anti-Texas Red, anti-DNP and anti-DIG). The accumulation of streptavidin-colloidal gold conjugate (40 nm) at respective areas produced positive results, seen as red dots within 15 minutes. The analytical sensitivity at DNA level of mPCR-LFA for S. enterica ser. Typhi and S. enterica ser. Paratyphi A were 0.16 ng and 0.08 ng, respectively, while mPCR-agarose gel electrophoresis were 0.63 ng for both. Validation of the mPCR-LFA using 100 bacterial isolates comprising of 25 S. enterica ser. Typhi, 25 S. enterica ser. Paratyphi A, 25 Salmonella serovars and 25 other bacteria as a proof of concept showed 100% sensitivity and specificity suggesting that the primers of the targeted genes were specific for S. enterica ser. Typhi, S. enterica ser. Paratyphi A and Salmonella serovars without cross-reactivity with DNA from other bacteria. Validation of the mPCR-LFA using spiked stool samples showed that the test can detect as low as 101 CFU/ml S. enterica ser. Typhi and 102 CFU/ml S. enterica ser. Paratyphi A. The mPCR-LFA also showed 100% sensitivity and specificity when validated using stool samples spiked with 100 bacteria isolates suggesting that the test was successfully developed without any inhibition. When stool samples from food handlers and suspected carriers were used in this mPCR-LFA, five out of 60 samples were positive and these results correspond to the culture results. As a conclusion, mPCR-LFA is a simple, rapid, sensitive and specific alternative method for the detection of typhoid and paratyphoid carriers compared to detection method BLASTn program were aligned using ClustalW Multiple Alignment (BioEdit software). Forward primers were labeled with FITC, Texas Red, DNP and DIG at the 5’end, while reverse primers were labeled with biotin at the 5’end for the purpose of detection using lateral flow assay. After amplification, labeled PCR amplicons were applied onto the lateral flow strip and bound to their respective capture reagents immobilized on the membrane (anti-FITC, anti-Texas Red, anti-DNP and anti-DIG). The accumulation of streptavidin-colloidal gold conjugate (40 nm) at respective areas produced positive results, seen as red dots within 15 minutes. The analytical sensitivity at DNA level of mPCR-LFA for S. enterica ser. Typhi and S. enterica ser. Paratyphi A were 0.16 ng and 0.08 ng, respectively, while mPCR-agarose gel electrophoresis were 0.63 ng for both. Validation of the mPCR-LFA using 100 bacterial isolates comprising of 25 S. enterica ser. Typhi, 25 S. enterica ser. Paratyphi A, 25 Salmonella serovars and 25 other bacteria as a proof of concept showed 100% sensitivity and specificity suggesting that the primers of the targeted genes were specific for S. enterica ser. Typhi, S. enterica ser. Paratyphi A and Salmonella serovars without cross-reactivity with DNA from other bacteria. Validation of the mPCR-LFA using spiked stool samples showed that the test can detect as low as 101 CFU/ml S. enterica ser. Typhi and 102 CFU/ml S. enterica ser. Paratyphi A. The mPCR-LFA also showed 100% sensitivity and specificity when validated using stool samples spiked with 100 bacteria isolates suggesting that the test was successfully developed without any inhibition. When stool samples from food handlers and suspected carriers were used in this mPCR-LFA, five out of 60 samples were positive and these results correspond to the culture results. As a conclusion, mPCR-LFA is a simple, rapid, sensitive and specific alternative method for the detection of typhoid and paratyphoid carriers compared to detection method by agarose gel electrophoresis. The development of mPCR-LFA is one of the ways in making the diagnostic tests accessible to developing and underdeveloped countries.